STRATEGY IN AVOIDING CONFLICT MULTICULTURAL SOCIETY (Case Study: Community In Nagari Koto Baru District Luhak Nan Duo West Pasaman) - Debora, Elly Kristin; Anggreta, Dian Kurnia; Yasin, Faishal (Pendidikan Sosiologi, 2013)
Nagari Koto Baru Society is a Multicultural society consisting of a variety of ethnic groups , where each tribe had a different culture . Although the Nagari Koto Baru has a diversity of ethnic groups , but in Nagari Koto Baru conflict never happened . In this study that will be examined is what causes the multicultural society in Nagari Koto Baru District Luhak Nan Duo West Pasaman avoid conflict and how the multicultural society strategies in Nagari Koto Baru in avoiding conflict . The research was conducted for the three months May to July. The analysis in this study using structural and functional theories of conflict strategies . The method used is descriptive method with qualitative approach . Data collection tools such as in-depth interviews , non - participant observation , and document . This research was conducted on 23 informants , with the aim of describing the cause of the multicultural society in Nagari Koto Baru District Luhak Nan Duo West Pasaman in avoiding conflict and multicultural society strategies in Nagari Koto Baru District Luhak Nan Duo West Pasaman in avoiding conflict. Research in the field indicates that the cause of the multicultural society in Nagari Koto Baru District Luhak Nan Duo West Pasaman avoid conflicts caused by two factors: solidarity and marital factors. Strategy undertaken by Nagari Koto Baru in avoiding conflict is to make a process of cooperation , accommodation and assimilation